The effectiveness of gamification in learning Arabic phrases - Mohd Ismath, Nurul Hanilah; Abd Aziz, Abdul Hadi (Korint Publishing, 2025)
In this era of Information and Communication Technology, a lot of educators use the technology provided on the Internet to attract students to focus on learning. This study aims to investigate the effectiveness of using gamification in learning Arabic language phrases at the intermediate level of Arabic language proficiency. This research explores the effectiveness of gamification in facilitating the acquisition of Arabic as a second language. The study employs a qualitative approach which involves students of Arabic online course. Four students were interviewed as participants for this qualitative method. The data was analysed using Thematic Analysis for the interview. The findings show that using gamification helps them understand Arabic sentences and gives them numerous examples of verbs and nouns in creating good Arabic phrases. The findings suggest that using gamification as a learning tool could promote fun learning. The implications of gamification on the students to understand and use the correct phrase when communicating in Arabic for the intermediate level and as a tool for educators to encourage students to engage in Arabic proficiency. In conclusion, gamification in learning Arabic phrases is a catalyst for interactive Arabic learning.